Estimation of prevalence of risk factors for coronary artery disease in a rural population in Howrah, West Bengal - Pattnayak, Ujjwal; Banerjee, Debdutta; Madhwani, Kishore P.; Singh, Jitendra Kumar (International Journal Of Community Medicine And Public Health, 2019)
Background: Coronary artery disease (CAD) is a major cause of death globally in both developed and developing countries. Coronary artery disease which was once thought to be a disease of the urban population is now involving the rural community in an increased number. So a study of major coronary risk factors in rural communities will help to adopt various strategies particularly behavior change and communication relevant for these communities to prevent these risk factors and lower CAD related mortality and morbidity. Objective was to estimate rates of the various risk factors for CAD and identify the high-risk groups in the rural community. Methods: A community based cross sectional study was carried out in a rural area in the Howrah district of West Bengal. Four hundred and eighteen (418) persons (212 males and 206 females) were subjected to study using structured, pretested and predesigned schedule. Coronary artery disease risk factors were assessed. Statistical analysis was done with the help of statistical software, the SPSS 20.0 for windows. Results: The study observed that prevalence of tobacco use among the study population was the most significant risk factor (42.3%). The prevalence of other coronary risk factors ranged from 10-20%. Tobacco use, alcohol consumption and sedentary life style were significantly more amongst males. Whereas truncal obesity and systolic hypertension more among females. Conclusions: Various comprehensive strategies particularly behavior change and communication targeting these high risk population need to be emphasized to lower CAD related morbidity burden in the community.